The IMF to the rescue: Did the euro area benefit from the fund's experience in crisis fighting? - Sebastian Dullien; Barbara Fritz; Laurissa Mühlich (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2016)
The paper analyses how the IMF brought its experience gained in emerging market sovereign debt crises in the troika's handling of the euro crisis. We link models of multiple equilibria with the IMF's experience made in Latin American crises in the 2000s. We examine subsequent changes in the IMF's policy guidelines and show that previous insights have been taken in, but applied only with a significant delay and partially against institutional rules and internal advice for the case of Greece. Hence, we argue that the inclusion of the IMF in Europe's crisis fighting did not completely deliver what had been hoped for.
Keywords: 330; euro crisis; emerging market debt crisis; IMF; multiple equilibria; sovereign debt resolution mechanism